"THE ROLE OF FINANCIAL INCLUSION IN POVERTY REDUCTION" (International Journal of Food and Nutritional Sciences, 2022)
Financial inclusion plays an important role in reducing poverty by providing access to formal financial services to individuals and families traditionally excluded from mainstream financial systems. This paper explores the relationship between financial inclusion and poverty reduction and examines the mechanisms through which financial inclusion can reduce poverty. It examines the impact of various financial services such as savings, credit, insurance and payment systems on poverty. The study employs a mixed-methods approach combining quantitative data analysis and qualitative case study. The findings indicate a significant negative correlation between financial inclusion indicators and poverty measures. Increased access to financial services is associated with improvements in income, consumption and wealth accumulation, thereby reducing poverty. However, challenges such as financial literacy, access barriers, and regulatory hurdles hinder the widespread adoption of financial inclusion, especially among marginalized populations. The paper emphasizes the importance of financial inclusion as a catalyst for inclusive economic growth and provides recommendations to overcome barriers and promote sustainable poverty reduction.